Rethinking Taxonomies: Towards a Coherent Outlook on the Textual History of Revelation - Malik, Peter (Novum Testamentum, 2025)
For centuries, philologists have employed various taxonomies to textual traditions they studied, the New Testament being no exception. In recent decades, however, serious doubts have been cast on their validity, particularly in the light of new methods such as the Coherence-Based Genealogical Method (CBGM). And yet, the Book of Revelation had stood on the fringe of such methodological discussions. The present article aims to remedy this. Firstly, the authors shall review the most salient previous research into the textual history of Revelation, with a particular focus on text types. After that, they shall outline their own proposal for depicting the textual tradition, informed by the application of the CBGM.